Suicidality among Hong Kong nurses: prevalence and correlates. (29th December 2015) - Cheung, Teris; Lee, Paul H.; Yip, Paul S.F.
Abstract: Aims: The study estimates the prevalence and examines the socio‐economic and psychological correlates of suicidality among professional nurses in Hong Kong. Background: Suicide rates among middle‐aged employed groups have been increasing over the past few decades. There is a concern that medical occupational groups worldwide are at elevated risk of suicide. Nonetheless there are few population‐based studies of suicide dealing with working‐age Asian nurses. Design: The study uses a cross‐sectional survey design. Method: Data were collected in Hong Kong over 4 weeks from October–November 2013. Statistical methods including descriptive analysis and univariate and multivariate cumulative logit modelling were used to examine the weighted prevalence rates of past‐year suicidality and its associated factors in nurses. Results: A total of 850 nurses participated in the study; 14·9% of participants had contemplated suicide while 2·9% had attempted suicide once or more in the past year. Women report suicidal thoughts or attempts more often than men. Religion, poor health, deliberate self‐harm, depressive symptoms and poor self‐perceived physical and mental health were significantly associated with nurses' suicidality. Conclusions: Nurse professionals are not immune from mental health issues. Hong Kong's local health authority should put in place a raft of suicide prevention initiatives to promote mental wellness in the profession.